Graduate band conducting recital: lesson plans and theoretical/historical analysis of literature - Kongs, Veronica Louise (Kansas State University, 2007)
This report contains lesson plans as well as a theoretical and historical analysis of the literature performed in the Graduate Conducting Recital of Veronica Kongs. The recital was held in the Satanta Junior/Senior High School Auditorium in Satanta, Kansas on Tuesday, May 8, 2007 at 7:00 p.m. The recital featured performances by the Junior High and High School Concert Bands. Literature for the Junior High Concert Band included Korean Folk Rhapsody arranged by James Curnow and Riders on the Southern Front by Roland Barrett. The Junior High/High School Concert Band literature consisted of For Thy Courts Above by Ed Huckeby and Of Dark Lords and Ancient Kings by Roland Barrett. This report utilizes two analytical methods, the Larry Blocher/Richard Miles Unit Study model used in the Teaching Music through Performance in Band Books and the Frank Tracz approach of macro-micro score analysis.
Keywords: Rehearsal lesson plans for concert band conducting recital; Korean Folk Rhapsody arranged by James Curnow; Riders on the Southern Front by Roland Barrett; For Thy Courts Above by Ed Huckeby; Of Dark Lords and Ancient Kings by Roland Barrett; Education, Music (0522); Music (0413)